Pengaruh Profesionalisme dan Kompetensi Auditor terhadap Kualitas Audit dengan Pengalaman Kerja Sebagai Variabel Moderasi - Widyawati, Titis Indah; Dahlan, Ahmad (Juara: Jurnal Riset Akuntansi, 2024)
The audit profession is trusted by the general public. Public trust in the quality of audit reports is currently in crisis due to the rise of scandals involving Public Accounting Firms. To win back the trust of their customers, auditors must demonstrate improvements in audit quality based on a professional attitude, competence, and work experience. The aim of this research is to reveal the influence that the relationship between professionalism and auditor competence has on audit quality which is moderated by work experience. The research population consisted of 83 auditors from 15 Public Accounting Firms) in the Greater Malang area, and the sampling approach used was purposive sampling. Primary data sources and quantitative data were used in this research. The analysis technique used is a structural equation model based on Partial Least Square (SEM-PLS). The research results show that professionalism has an impact on audit quality, while auditor competence has no impact on audit quality. Work experience has no impact on the influence of auditor professionalism and competence on audit quality. On the other hand, competency has no effect on audit caliber. The results of this research can be used as evaluation material by auditors in the Greater Malang area to improve the quality of their audits.